Depression, anxiety, stress, and coping among men with infertility seeking treatment at a tertiary care hospital in South India: A mixed-method study - Mamta Mor; Venkatachalam Jayaseelan; Shivanand Kattimani; Chitra Thyagaraju; NS Kubera; Mahadevan Duraiswamy (Indian Journal of Psychiatry)
Background: Many studies in India and all over the world have focused on the psychological aspect of infertility in women, but only a few have explored it among men. To deal with psychological distress, sometimes, individuals may use maladaptive coping strategies which can further worsen the stress instead of reducing it. Aim: To assess symptoms of depression, anxiety, stress, and various coping strategies adopted by men with infertility along with exploring their coping experiences. Methods: A sequential explanatory mixed-method study was conducted in a tertiary care hospital in South India. The study was conducted among 200 men with infertility seeking treatment from a tertiary care hospital. The symptoms of depression, anxiety, and stress were assessed using Depression, Anxiety, Stress-21 scale, and coping strategies were assessed using Brief COPE scale. In-depth interviews were conducted among eight men who had moderate to severe symptoms of depression, anxiety, and stress. Results: The proportion of depressive symptoms was 46% (95% CI: 39.2–52.9), that of anxiety was 51% (95% CI: 44.1–57.8), and that of stress was 59.5% (95% CI: 52.5–66.0). The most common coping strategies used were planning (96.0%), active coping (91.5%), self-distraction (90.5%), and religion (89.5%). The analysis of qualitative data revealed three themes – emotional impact of infertility, coping mechanisms and support systems, and perception toward counseling to improve mental wellbeing. Conclusion: The study shows that the prevalence of symptoms of depression, anxiety, and stress is considerable among men with infertility. The majority of them were using problem-focused coping. Overall, the study highlights the need to diagnose and address mental health problems among men with infertility.